Innovation of the “Tumbas” marketplace: Policy network analysis in the empowerment of small and medium industries in Mojokerto Regency - Tsabitah Mariyah Dwiyanti; Kalvin Edo Wahyudi (Universitas Muhammadiyah Malang, 2025)
Empowering Small and Medium Enterprises (SMEs) through a policy network approach has rarely been studied in depth, particularly in the context of marketplace innovation. This study examines how policy networks contribute to SME empowerment through the